1993
DOI: 10.1111/j.1600-0447.1993.tb03378.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and amino acid content in platelets of autistic children

Abstract: The platelet levels of serotonin and the amino acids aspartic acid, glutamine, glutamic acid and gamma-aminobutyric acid were measured in 18 drug-free autistic (DSM-III criteria) and 14 age-matched healthy children. Serotonin was significantly increased while the amino acids aspartic acid, glutamine, glutamic acid and gamma-aminobutyric acid were significantly decreased in comparison with the controls. It is suggested that the decline of the amino acids in platelets from autistic children represents a biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 13 publications
1
72
0
1
Order By: Relevance
“…97,98 Serotonin has wide-ranging effects on physiological processes in the nervous, GI, and immune systems. Antibodies directed against serotonin receptors have also been reported in ASD, 62,99 suggesting that the availability of serotonin may be different in ASD.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…97,98 Serotonin has wide-ranging effects on physiological processes in the nervous, GI, and immune systems. Antibodies directed against serotonin receptors have also been reported in ASD, 62,99 suggesting that the availability of serotonin may be different in ASD.…”
Section: Neurotransmittersmentioning
confidence: 99%
“…17 Finally, disturbed glutamate concentrations have been reported in autistic patients compared to controls, with high levels in plasma 18 and low levels in platelets. 19 In the present study, we present the complete genomic structure of the human GluR6 gene, including new isoforms, linkage/association analyses in autistic subjects and the nucleotide variations present in the gene. These studies support the hypothesis that GluR6 may be a susceptibility gene for autism.…”
Section: Introductionmentioning
confidence: 99%
“…Blood plasma glutamate levels have been found to be increased (Hassan et al, 2013) and platelet levels of its precursor glutamine, decreased (Rolf, Haarmann, Grotemeyer, & Kehrer, 1993) in participants with ASD compared to neurotypical controls. Similarly, whilst Dhossche et al (2002) reported higher blood plasma GABA levels in children with ASD, decreased platelet levels of GABA have also been reported (Rolf et al, 1993).…”
Section: Blood Measurementmentioning
confidence: 99%